Bifurcations in a Leslie-Gower type predator-prey model with a rational non-monotonic functional response - González-Olivares, Eduardo; Mosquera-Aguilar, Adolfo; Tintinago-Ruiz, Paulo; Rojas-Palma, Alejandro (Mathematical Modelling and Analysis, 2022)
A Leslie-Gower type predator-prey model including group defense formation is analyzed. This phenomenon, described by a non-monotonic function originates interesting dynamics; positiveness, boundedness, permanence of solutions, and existence of up to three positive equilibria are established. The solutions are highly sensitive to initial conditions since there exists a separatrix curve dividing their behavior. Two near trajectories can have far omega-limit sets. The weakness of a singularity is established showing two limit cycles can exist. Numerical simulations endorse the analytical outcomes.